Minimum existential and possible reserve in health lawsuits and the consequences for the principle of equality (Research, Society and Development, 2021)
The Federal Constitution of 1988 established a social state, guaranteeing rights understood as essential that would be supported by the community, among them, the social right to health. However, the budgetary availability of the State is not sufficient to fully guarantee social rights for all. In this antinomic context lawsuits emerge, a moment in which the discussion refers to the guarantee of the State to the minimum existential to a dignified life and the principle of possible reserve. Furthermore, when a certain drug is granted, individually, through a court decision, it ends up circumventing the criteria of equality established for the public health policy in Brazil. That said, the present study addresses the State in its political aspect, as a guarantor of rights, with a focus on the supply of medicines. For this purpose, the concepts of minimum existential and possible reserve were rescued, through exploratory documentary research, making an analysis of the impacts for the principle of equality, aiming to avoid controversies regarding the prevalence of the right to health. In the end, it was found that the Public Power has the necessary tools to optimize the management of resources and improve constitutional effectiveness.